SEJARAH KOTA SURABAYA DALAM MATERI KETERAMPILAN MENYIMAK UPAYA INTERNASIONALISASI BAHASA PADA KELAS DARMASISWA UNIVERSITAS MUHAMMADIYAH SURABAYA TAHUN 2019/2020 - Kartika, Pheni Cahya; Kusnarto, Kusnarto (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia)
Language Internationalization has long been sparked and is the mission of academics who always fight for Indonesian as a national identity. A variety of ways including promoting the culture of Indonesia that are attractive to foreigners aim to want to learn languages and cultures that are referred to as foreign speakers. Surabaya as one of the biggest cities in Indonesia becomes a reference in knowing the culture such as Javanese culture, typical dialect language, history of heroism and historical attractions of the city. The explicit problem is to introduce the history of the city of Surabaya in learning materials in the class listening to the Darmasiswa class. Understanding history is expected to be a bridge in knowing culture and bringing Indonesian to be easily studied by foreign speakers, it is also to find out the success of students in listening to the history material of the city of Surabaya. The research method through a qualitative descriptive approach with the results of data analysis of interviews and observations of learning in class, is expected to form a learning based on local wisdom that is more devoted to the history of the city of Surabaya able to obtain learning objectives, especially success in knowing the language and culture in the effort to internationalize Indonesian.